Acceptability, feasibility, and program outcomes of an equity-focused, adapted community-based healthy lifestyle program for children, young people, and their families in Perth, Western Australia: an implementation hybrid research protocol - Smith, Stephanie; Paull, Stephen; Iwanowski, Katie M.; Harris, Tania; Moullin, Joanna C.; Jane, Monica; Bill, Jordan; Kerr, Deborah A.; Pollard, Christina M.; Pearson, Glenn; Robinson, Melanie; Furzer, Bonnie; et al. (Frontiers in Health Services, 2025)
BackgroundInternational guidelines recommend multidisciplinary intervention programs for addressing childhood obesity. In Western Australia, community-based healthy lifestyle programs for children and young people are insufficient for demand, especially for those over-represented in obesity statistics relating to prevalence. This protocol outlines the implementation and evaluation of an adapted, evidenced, community-based program in Perth, Western Australia.MethodsThis study follows a multiple-methods hybrid type II design, testing acceptability and feasibility of program scale-out and program participant outcomes. Study (1) Develop the adapted healthy lifestyle program with key partners and Aboriginal and Torres Strait Islander advisors for scale-out. Apply implementation strategies for program realisation. Identify critical elements and outcomes to demonstrate program success with key partners (∼30 workshop participants and ∼80 qualitative proforma respondents). Identify cultural and place-based considerations for program acceptability with Aboriginal and Torres Strait Islander Elders/advisors (∼30 workshop participants). Study (2) Assess acceptability, appropriateness, feasibility, and local clinical outcomes of adapted healthy lifestyle program pilot. Evaluate the program with children and young people aged 4–16 years with obesity or overweight and weight-related comorbidities, seeking healthy lifestyle change. The program will include weight-related assessments at baseline, 6, and 12 months with weekly sessions for 6 months (estimated n = 245 over 22 months, accounting for 30% drop-out). Explore program experience via focus groups with children, young people, and caregivers: ∼8–12 weeks post commencement (∼50 program participants and caregivers), ∼6 months post commencement (∼50 program completers and caregivers), and evaluation survey (e.g., declined/dropped out/completed). Engage with key partners to determine program feasibility for scale-up (∼30 workshop participants and ∼80 qualitative proforma respondents). Mixed model regression will be used to assess within-subject change in outcomes over time. Child health utility instruments will be used for cost-utility analysis. Study (3) Assess program scalability post-pilot. If determined feasible and acceptable, the program will be packaged to assist practitioners and policymakers with scale-up via exploration of currently available packages and key staff interviews. The overarching Replicating Effective Programs framework outlines the implementation stages, and the tools and strategies being applied are presented. Qualitative data will be analysed using Framework Analysis, incorporating the Consolidated Framework for Implementation Research and the Expert Recommendations for Implementing Change.DiscussionImplementation outcomes will be determined by evaluating acceptability, appropriateness, and feasibility of scale for this healthy lifestyle program. Utilising implementation science, partnership-building, and place-based and cultural considerations, this research will inform potential scale-up of equity-focused healthy lifestyle programs.